Physico-chemical characterization of the fat from red-skin rambutan (nephellium lappaceum l.) seed - Abdul Manaf, Yanty Noorziana; Marikkar, Mohammed Nazrim; Long , Kamariah; Mohd Ghazali , Hasanah (Japan Oil Chemists' Society, 2013)
The seeds of the red skin rambuttan (Nephelium lappacaceum L) contains a considerable amount of crude fat (38%) and, thus the aim of the study was to determine the physico-chemical properties of this fat for potential applications. The iodine and saponification values, and unsapponifiable matter and free fatty acid contents of the seed fat were 50.27 g/ 100 g fat, 182.1 mg KOH/ g of fat, 0.8% and 2.1%, respectively. The fat is pale yellow with a Lovi-bond color index of 3.1Y + 1.1 R.The fatty acid profile indicates an almost equal proportion of saturated (49.1%) and unsaturated fatty acid (50.9%).